Tunable kinetics of nanoaluminum and microaluminum powders reacting with water to produce hydrogen. (12th August 2019) - Saceleanu, Florin; Vuong, Thu V.; Master, Emma R.; Wen, John Z.
Summary: This paper reports on the kinetics and reaction processes of 40‐nm and 1‐μm aluminum powders with water to produce hydrogen at atmospheric pressure. This reaction produces aluminum hydroxide with irregular morphologies as by‐products. It was found that the nucleation and growth of the aluminum hydroxides affect the kinetics of the reaction and thus the hydrogen production. The heat release in isothermal microcalorimetry and hydrogen production in a nonisothermal batch reactor were used to determine the rate‐determining steps of the reaction mechanism and the corresponding activation energies. Model and model‐free methods have been implemented to describe the reaction sequence between aluminum particle and water while the phase of newly produced aluminum hydroxide in the system plays an important role. The reaction of nanoaluminum particles and water, being more sensitive to temperature, goes to completion to produce bayerite, Al (OH)3 at 30°C, and boehmite, AlOOH at 50°C, whereas the microaluminum particles do not react completely and produce only bayerite at 30°C and also low‐amount boehmite at 50°C. Nevertheless, these processes exhibit two distinct and sequential stages: a kinetically controlled stage with the apparent activation energy ( E a ) of 100 to 110 kJ/mol, where nucleation and growth are limited by the chemical reactions on the surface of aluminum, and a diffusion controlled stage with E a of 44 kJ/mol for the 40‐nm Al/water reaction and 86 kJ/mol for the 1‐μm Al/water reaction, where growth is limited by the mass diffusion through the aluminum hydroxide by‐products. The separation of these two stages is more obvious under isothermal conditions. For nonisothermal conditions, two stages are overlapped, and the one with a lower E a dominates. Abstract : The manuscript entitled "Tunable kinetics of nanoaluminum and microaluminum powders reacting with water to produce hydrogen" by Florin Saceleanu, Thu V. Vuong, Emma R. Master, and John Z. Wen reports on the complex reaction mechanism between aluminum particles and liquid water during hydrogen production. Isothermal and nonisothermal experiments indicate that these exothermic reactions are complicated by mass transport and the overall mechanism is found by the nucleation and growth model. The apparent activation energy varies with the extent of the reaction according to the two rate‐controlling stages. In nonisothermal experiments, the kinetic stage is overshadowed by the diffusion stage due to the lower apparent activation energy of the latter.